Kualitas Pelayanan Puskesman dalam Mengukur Kepuasan Masyarakat - Alamsyah, Alamsyah; Handoko, Rudi (Universitas 17 Agustus 1945 Surabaya, 2019)
Service quality can be interpreted as the level of satisfaction of guests or consumers. While this level of satisfaction itself can be obtained from a comparison or type of service that is actually received by consumers. By using the Community Satisfaction Index of the year 14 of 2017 conducted at the Borong Rappoa kecamatan puskesmas. Kindang district. Provincial Bulukumba. South Sulawesi's quality of service at the Borong Rappoa health center still found deficiencies such as more discriminating people who would seek treatment at the Borong Rappoa Health Center, as well as limited facilities and infrastructure. So based on the above problems, the focus of the problem formulation is How is the Quality of Service provided by the Borong Rappoa Kec Hemat Health Center. Kindang Regency. Bulukumba Province of South Sulawesi? This study is to determine the quality of Puskesmas services. In this study using the survey method, which uses observation and interview data and uses a qualitative approach with descriptive research types. The results showed that with the results of the data analysis, it was concluded that the research entitled